Building Eco-Theological and Bio-Centric Approach to Environmental Ethics: John B. Cobb’s Perspective - Md. Abu Sayem (Religio: Jurnal Studi Agama-agama, 2021)
This paper discusses John B. Cobb’s interpretation of Christian ecological moral foundation based on his “process theological” understanding as well as his critics to traditional Christian view of human supremacy over non-human creatures. It aims to explore Cobb’s eco-theological understanding based on bio-centric environmental approach and explore why his eco-theological thought becomes significant for the ongoing discourses on environmental ethics, especially from religious perspectives. This research also describes how Cobb’s idea could be working for sustainability of environment. In so doing, this paper enriches the current discussions on environmental ethics from Christian eco-theological perspective.